Gestión administrativa en el Almacén Artefacta de la parroquia San Juan en el periodo 2023. - Minda Mariscal, Alejandrina Marisol (2025)
This research study was conducted at Almacen Artefacta de San Juan, the variable addressed is administrative management, which is particularly relevant because a large part of a company's results depend on a good application of administrative principles. The objective is to analyze the way in which administration is managed in the aforementioned company in order to identify relevant aspects that need to be improved. The methodology used corresponds to a non-experimental design with descriptive cut, here two investigative techniques are applied: the survey directed to the administrator and a survey focused on the rest of the collaborators, this allows contrasting the information of the primary sources that participate in this study. The results show that there are weaknesses in the administrative function, since they do not have a management model that guarantees the fulfillment of the organizational objectives in the medium and long term, so that practical adjustments are required to contribute significantly to the improvement of the current situation, so that the company achieves greater competitiveness in the market in which it operates. The conclusion reached is that there is a need to increase the administrative strategies, since the ones that are implemented at the moment are not generating the expected results.